Autores - Rivas, Ramón D. (Kóot, 2017)
Chester Urbina GaitánErnesto Rivas ArévaloHéctor SamourDr. Jorge Alberto Amaya BanegasJulián Barrera TolentinoElisa PritzkerSigfredo Cabrera RajoRubén FúnezRamón D. RivasJulio MartínezMario Bencastro